Balance and fatigue in wrestlers - Letafatkar, A.; Shojaeddin, S.; Amirsasan, R.; Taghavi, M. (International Journal of Wrestling Science, 2012)
The purpose of this study was to show that: being "in context" and "similarity" in fatiguing protocols to the main aspects of sport does not alter wrestlers balance. Methods: Twenty professional male wrestlers (age 26.2±1 yr, VO2max 62.3±3.1 ml kg min) participated in this study (10 in experimental and 10 subjects in control group) and completed a fatigue protocol. In this study, a regular wrestling match was used for the metabolic fatigue protocol. Biodex® balance system and lactometer were used for evaluation of balance and blood lactate level (respectively). For statistical analysis, the Pearson correlation coefficient, paired t-test, sample t and ANOVA tests were used. Results: Based on these study results, the static balance alterations in the experimental group (eyes open and eyes closed positions) were respectively 0.16% and 3.17%, and this was not statistically meaningful. Also, dynamic balance alterations in the experimental group (eye opened and eye closed positions) were 0.12% and 0.41% (respectively) which was not statistically meaningful. There was not a significant relationship between lactate acid accumulation and variations of the stability indices (r=-0/570, p<0.05). Conclusion: one of the best explanations for the absence of alteration in wrestlers balance is that: the fatiguing protocol exerted in this study is "in context" and "similar" to wrestling training and this can cause the wrestlers to utilize an anticipatory postural adjustment system for further maintaining postural stability. The possible mechanisms responsible for limiting the effect of fatigue on static and dynamic stability include: an alteration in afferent sensory inputs, a decrease in postural adjustment, increase in COP displacement, increase in delay time and decease in muscular activity, alteration in proprioception and the dysfunction of contractile units in anti gravity muscle following fatigue.